The feasibility of Al-Faruqi’s meta-religion principles: Sharing of research experience - Ibrahim, Haslina (2013)

(untitled)
This paper shares part of the research experience in applying al-Faruqi’s meta-religion principles for developing profile of religions in Malaysia. To capture the principles, two major categories have been recommended as the anchoring themes which are ‘permanent’ and ‘dynamic’. The categories were tested by means of in-depth interviews with learned representatives of four major religions in Malaysia. This paper therefore focuses on sharing parts of the important processes involved in the research those are developing and testing the themes and the questions. The two processes have enlightened the researcher on the feasibility and the weaknesses of meta-religion principles as means for understanding religions